(untitled) (Muitas Vozes, 2024)
This essay aimed to explore some excerpts from Clarice Lispector’s personal correspondence with her sisters during the years she lived outside Brazil (1944 and 1959); based on the issue of exile. The theme of exile was directed towards ‘being outside’, either in terms of territorial uprooting or as a condition of existence. For that, we used the letters organized in the book Minhas Queridas (2007), compiled by the biographer Tereza Montero, in addition, we resorted to the theoretical contributions of Edward Said and Jean-Luc Nancy. We understand that to think of exile in Clarice is to think of it as one’s own, not as a property, but as an opening to the world, as proximity in the distance; Clarice’s personal experience and experience as a writer testify to language and existence as a foreigner and, at the same time, as an opening of being-in-the-world, which means movement of being. With that, the ‘being outside’ in addition to crossing the speeches, it can also be considered a ‘productive network’ not only for the writer’s personal life, but for the richness of the context of her literature.